TAK1 knock-down in macrophage alleviate lung inflammation induced by black carbon and aged black carbon. (October 2019) - Cheng, Zhiyuan; Chu, Hongqian; Wang, Siqi; Huang, Yao; Hou, Xiaohong; Zhang, Qi; Zhou, Wenjuan; Jia, Lixia; Meng, Qinghe; Shang, Lanqin; Song, Yiming; Hao, Weidong; et al.
Abstract: Black carbon (BC) can combine with organic matter and form secondary pollutants known as aged BC. BC and aged BC can cause respiratory system inflammation and induce lesions at relevant sites, but the underlying mechanism has remained unknown. To gain insight into the potential mechanisms, we focused on macrophages and transforming growth factor β-activated kinase 1 (TAK1) which are a crucial factor in inflammation. Our research aims to determine the role of TAK1 in macrophages in pulmonary inflammation induced by particulate matter. In this study, BC and 1, 4-naphthoquinone were mixed to model aged BC (1, 4NQ-BC) in atmosphere. BC induced mice lung inflammation model, lung macrophage knock-down TAK1 animal model and primary macrophage knock-down TAK1 model were used to explore whether TAK1 in macrophage is a critical role in the process of inflammation. The results showed that the expressions of inflammatory cytokines (IL-1β, IL-6, IL-33) mRNA were significantly increased and the phosphorylation of MAPK and NF-κB signaling pathway related proteins were enhanced in RAW 264.7 cell lines. In vivo studies revealed that the indicators of pulmonary inflammation (pathology, inflammatory cell numbers) and related cytokines (IL-1β, IL-6, IL-33) mRNA expressions in CD11c-Map3k7 −/− animals were significantly lower than wild-type animals after mice were instilled particles. In mice primary macrophages, the expressions of IL-6, IL-33 mRNA were inhibited after TAK1 gene was knock-down. These results unequivocally demonstrated that TAK1 plays a crucial role in BC induced lung inflammation in mice, and we can infer that BC and 1, 4NQ-BC cause these inflammatory responses by stimulating pulmonary macrophages. Highlights: BC has different physico-chemical properties compared with 1, 4NQ-BC. TAK1 knock-down in macrophages could alleviate mice lung inflammation induced by BC and 1, 4NQ-BC. TAK1 plays a key role in the production of IL-33 by macrophages.